The Differences in the dentition pattern in monozygotic twins based on panoramic examinations – case report on two pairs of twins - Miazek, Weronika; Smala, Kamila; Piskórz, Magdalena; Różyło-Kalinowska, Ingrid; Futyma-Gąbka, Karolina (Journal of Education, Health and Sport, 2023)
The aim of the study is to present two examples of twins with differences in their dentition revealed with the use of panoramic examinations. The analysis based on panoramic X-rays shows that even though the monozygotic twins share 100% of the genome, their dentitions reveal significant differences.